-2(3x-5)+4=-6x+14

Simple and best practice solution for -2(3x-5)+4=-6x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3x-5)+4=-6x+14 equation:


Simplifying
-2(3x + -5) + 4 = -6x + 14

Reorder the terms:
-2(-5 + 3x) + 4 = -6x + 14
(-5 * -2 + 3x * -2) + 4 = -6x + 14
(10 + -6x) + 4 = -6x + 14

Reorder the terms:
10 + 4 + -6x = -6x + 14

Combine like terms: 10 + 4 = 14
14 + -6x = -6x + 14

Reorder the terms:
14 + -6x = 14 + -6x

Add '-14' to each side of the equation.
14 + -14 + -6x = 14 + -14 + -6x

Combine like terms: 14 + -14 = 0
0 + -6x = 14 + -14 + -6x
-6x = 14 + -14 + -6x

Combine like terms: 14 + -14 = 0
-6x = 0 + -6x
-6x = -6x

Add '6x' to each side of the equation.
-6x + 6x = -6x + 6x

Combine like terms: -6x + 6x = 0
0 = -6x + 6x

Combine like terms: -6x + 6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| .005ab+a=300 | | 9a+5b+7a+8b=0 | | 8x*12x= | | 15+n=n-15 | | 2ab+b=300 | | 7y+4(y-8)=3(y+1)-2 | | 2x+y=-83 | | 3z-18=15-5z | | -12+13=10+n | | x^2+dx+49=0 | | 36x^2+17x-35=0 | | 4+w=3 | | F(X)=7x^8-1x^4+1 | | 84=12s | | -w+2=-2w+7 | | -3x-7x=-12 | | -2+15=4b-4-3b | | 20+m+13+m=2 | | -5a+24+2a=7a-4a | | (8+5i)(2-5i)= | | X+12-(-4)=17 | | 12-2(x+1)=5 | | 8-3x+12=11 | | 0.3x-0.7x-27=1 | | 6x+10038=x-28483 | | 15-2x=41 | | -7(x-4)+8x=26 | | 2(r)-7=r+15 | | 11w-13w=4 | | 41-3n=2 | | 6x+9=15x | | n^2-3n-40= |

Equations solver categories